Race, Indigenous Movements and Other forms of democracy. Or a possible way to decolonize the racial brand - García, Rocío Soledad (Universidad Nacional de Villa María, 2020)
The following article aims to generate contributions, questions and tools to think about race as a hierarchical axis of bodies, memories and knowledge in Latin America. A network of categories is then presented: race, indigenous movements and other forms of democracy, articulated and analyzed from a decolonial perspective. What happens when racial marks are drawn as forms of domination in various spheres of social existence? The writing leads us to the visibility of collective subjects that inhabit the borders of the racially delimited, with their memories, languages ​​and forms of social organization. Can we find there other forms of democracy that discuss the hegemony of liberal democracy? The proposed categorical fabric leads us to a hopeful answer.